Spontaneous Acute Subdural Hematoma due to Intracranial Hypotension Secondary to Lumboperitoneal Shunt: A Case Report and Review of the Literature - Feyza Karagoz Guzey; Ozgur Yusuf Aktas; Azmi Tufan; Burak Eren; Mustafa Safi Vatansever; Ilker Gulec; Ebru Doruk; Murat Karacan; Erhamit Okutan; Abdurrahim Tas (Bagcilar Medical Bulletin, 2017)

(untitled)
Objective:To report a rare case with spontaneous intracranial acute subdural hematoma due to overdrainage of cerebrospinal fluid after lumboperitoneal shunting and to review the literature on this topic.Case report: A 53-year-old lady with spontaneous acute subdural hematoma developing 3 years after lumboperitoneal shunting for treatment of benign intracranial hypertension is reported. She was treated with shunt removal and hematoma evacuation.Material and Methods: We found 16 cases with intracranial bleeding developing spontaneously or after mild head injury after lumboperitoneal shunting. The characteristics of the patients were recorded, the outcome was given according to the Glasgow Outcome Scale, and a Glasgow Outcome Scale score from 1-3 was accepted as worse outcome. The factors affecting outcome were evaluated.Results: There were 10 females and 7 males aged 59.7±15.1 years. In most cases, the primary disease treated by lumboperitoneal shunting was hydrocephalus or benign intracranial hypertension. In 12 of the cases, the bleeding happened into the subdural space and in 5 into other compartments (intracerebral or subarachnoid bleeding). Five of the cases died, and 62.5% had a worse outcome. The only factor affecting outcome was the time span from lumboperitoneal shunting to intracranial bleeding. This time was significantly shorter in the patients with worse outcome (3.7 versus 38.6 months).Conclusions: Lumboperitoneal shunting may cause serious complications such as intracranial bleeding due to overdrainage of cerebrospinal fluid via shunt. Patients with lumboperitoneal shunting must be followed very closely for development of intracranial hypotension especially during the first few months after shunting.